2011
DOI: 10.1523/jneurosci.4735-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reduced White Matter Integrity Is Related to Cognitive Instability

Abstract: Increased performance variability has been demonstrated in several groups and conditions, including aging and cognitive decline. Structural brain characteristics underlying this phenomenon have so far been elusive. However, there is reason to expect that disconnectivity in associative pathways, whether caused by immature or degraded white matter (WM) tracts, will increase performance variability by neural noise. The aim of this study was to test whether the quality of WM, measured by diffusion tensor imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
107
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 62 publications
14
107
4
Order By: Relevance
“…Previous work suggests a dissociation exists between these RT metrics, with white matter integrity being associated with variability but not mean-RT (Bunce et al, 2010;Bunce et al, 2007;Fjell et al, 2011;Mella et al, 2013;Walhovd & Fjell, 2007) and in older samples with neuropathology, variability is a stronger predictor of group membership than mean-RT (e.g., Dixon et al, 2007). In contrast to this work, we found comparable results when using measures of IIV and mean-RT, and neither measure was uniquely predictive of WMH.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Previous work suggests a dissociation exists between these RT metrics, with white matter integrity being associated with variability but not mean-RT (Bunce et al, 2010;Bunce et al, 2007;Fjell et al, 2011;Mella et al, 2013;Walhovd & Fjell, 2007) and in older samples with neuropathology, variability is a stronger predictor of group membership than mean-RT (e.g., Dixon et al, 2007). In contrast to this work, we found comparable results when using measures of IIV and mean-RT, and neither measure was uniquely predictive of WMH.…”
Section: Discussioncontrasting
confidence: 77%
“…In healthy ageing, associations have been shown between IIV and white matter hyperintensities (WMH: Bunce et al, 2010;Bunce et al, 2007), white matter volume (Jackson, Balota, Duchek, & Head, 2012;Lovden et al, 2013;Ullen, Forsman, Blom, Karabanov, & Madison, 2008;Walhovd & Fjell, 2007) and diffusion tensor imaging metrics (e.g., FA -fractional anisotropy) (Deary et al, 2006;Fjell, Westlye, Amlien, & Walhovd, 2011;Mella, de Ribaupierre, Eagleson, & de Ribaupierre, 2013; Moy et al, 2011). Generally, RT variability and WMH in old age 4 these investigations show that greater behavioural variability is associated with poorer neuroanatomical integrity (i.e., increased WMH burden, reduced volume, and lower FA).…”
Section: Introductionmentioning
confidence: 99%
“…Only FA showed an age-independent relationship with IIV, with negative relationships in the splenium of the CC and in the left inferior fronto-occipital fasciculus. Fjell et al (2011) reported robust age-independent relationships between IIV and all tested DTI indices in 270 subjects aged 20 -83 years. Importantly, the two latter studies indicate that the associations between IIV and WM characteristics in adults are not restricted to the frontal lobes.…”
Section: Discussionmentioning
confidence: 87%
“…We administered a speeded version of the flanker task (Eriksen and Eriksen, 1974), similar to the task used by Debener et al (2005), Westlye et al (2009), andFjell et al (2011). An illustration of the task is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation